Investigation of Potential Pharmacokinetic Interactions Between Teneligliptin and Metformin in Steady-state Conditions in Healthy Adults - Nakamaru, Yoshinobu; Hayashi, Yoshiharu; Davies, Martin; Jürgen Heuer, Horst; Hisanaga, Noriko; Akimoto, Kei (Clinical therapeutics, 2015)
We assessed the effects of coadministration of metformin and teneligliptin on their pharmacokinetics in steady-state conditions relative to the administration of either drug alone. This was a Phase I, single-center, open-label, 2-way parallel-group study in healthy male and female subjects. Subjects in group 1 (n = 20) were administered 40 mg of teneligliptin once daily for 5 days, and 850 mg of metformin BID was added to ongoing teneligliptin for an additional 3 days. The subjects in group 2 (n = 20) were administered 850 mg of metformin BID for 3 days, and 40 mg of teneligliptin once daily was added to ongoing metformin for an additional 5 days. Pharmacokinetic outcomes were the AUC0–τ and Cmax of metformin and teneligliptin when administered alone or in combination. Ten male and 10 female subjects participated in each group (mean ± SD age 39.2 ± 11.6 years [range, 19–63 years] in group 1, 47.6 ± 11.9 years [27–64] in group 2; mean ± SD BMI 23.36 ± 2.45 in group 1, 24.56 ± 2.54 in group 2). One female subject in each group was withdrawn because of an adverse event (AE) (vomiting). All 20 subjects in each group were included in the safety analyses, and 19 subjects in each group were included in the pharmacokinetic analyses. The geometric least square means ratio (teneligliptin plus metformin/teneligliptin alone) for Cmax and the AUC0–τ for teneligliptin were 0.907 (90% CI, 0.853–0.965) and 1.042 (90% CI, 0.997–1.089), respectively. The geometric least square means ratio (metformin plus teneligliptin/metformin alone) for the Cmax and AUC0–τ for metformin were 1.057 (90% CI, 0.974–1.148) and 1.209 (90% CI, 1.143–1.278). The 90% CIs were within the prespecified threshold for equivalence (0.80–1.25), except for the AUC0–τ for metformin, which was increased by teneligliptin by 20% relative to metformin alone. In group 1, nine subjects experienced 25 AEs during treatment with teneligliptin alone and 10 subjects experienced 15 AEs during treatment with teneligliptin plus metformin. In group 2, eight subjects experienced 11 AEs during treatment with metformin alone and 11 subjects experienced 18 AEs during treatment with metformin plus teneligliptin. Two AEs in each treatment group were rated as severe. Results of in vitro experiments suggest that teneligliptin-mediated inhibition of organic cation transporter-2 does not increase metformin exposure. Coadministration of teneligliptin and metformin was well tolerated by these healthy subjects during the 8-day treatment period. Coadministration with metformin did not affect the pharmacokinetics of teneligliptin. Although coadministration with teneligliptin increased exposure to metformin, this change is unlikely to be clinically relevant. European Clinical Trials Database identifier: 2007-001511-29.